CREATION OF THE EUROPEAN CIVIL SOCIETY AS CARRIER OF THE EUROPEAN VALUES - Ковбасюк, А.О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
This study of the role of civil society in the processes of European integration is based on the analysis of Western researchers’ works. The European civil society as carrier of the European values is described as an actor acting on the common European level (as opposed to a generalized notion of „civil society of the united Europe”).